Therapeutic alliance in two treatments for adults with severe and enduring anorexia nervosa. Issue 8 (6th September 2013) - Stiles‐Shields, Colleen; Touyz, Stephen; Hay, Phillipa; Lacey, Hubert; Crosby, Ross D.; Rieger, Elizabeth; Bamford, Bryony; Le, Daniel
ABSTRACT Objective The aim of this study was to investigate the strength and role of therapeutic alliance in a trial comparing Cognitive Behavioral Therapy for anorexia nervosa (CBT‐AN) and Specialist Supportive Clinical Management for the treatment of severe and enduring AN (SE‐AN). Method Participants were 63 adult females with SE‐AN presenting to an outpatient, multisite randomized controlled trial conducted at two clinical sites. Participants completed measures assessing their perception of the quality of the therapeutic relationship, eating disorder (ED) symptomatology, and depressive symptomatology. Results Beyond the effect of early treatment change and treatment assignment, early therapeutic alliance was a significant predictor of Restraint and Shape Concern at follow‐up (ps < .02). Late therapeutic alliance was a significant predictor of weight change, depressive symptomatology, and ED symptomatology at end of treatment and follow‐up (ps < .008), with the exception of Shape Concern at follow‐up (p = .07). Discussion The results suggest that therapeutic alliance can be effectively established in the treatment of SE‐AN and may be relevant for treatment response, particularly in late treatment, on some aspects of ED and depressive symptomatology. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:783–789)